(3GdbUjOI GdocejJjIs - (3GdcejJ Hf RjO Hf NfS GdCSOj, CHh GdeSJgd,J (B126 (3g` s ((3Ydj Hf RjO Hf CMeO Hf ESMGb Hf jMji Hf CHj jMji s)
(3ChdgG (B:s
(3Cde JJYLHj ef QjH OgmQ QCjJ XghQg bdHJ oHWhfkG s
(3BNQgG (B:s
(3hdh Cf Ce GdYfcHhJ HfJ dge eXdJgG jhe GddbGA CXdJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3Hbde eged GdfbW CMjGfkGs
(3HgG Jedc SfI (B1319(3g`s
(3cJHJ ddabjg Jbi GdOjf CMeO Hf ehSis
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs